PENGUATAN MANAJEMEN PEMASARAN DESA WISATA TRAH AJI KABUPATEN TEMANGGUNG JAWA TENGAH - Ignatius Agung Satyawan; Arofah Minasari; Rezza Dian Akbar (PROSIDING SERINA, 2021)
Tourism industry nowadays, especially before the COVID-19 outbreak, is experiencing rapid development. The tourism sector has contributed foreign exchange for national income. This is in line with the increasingly varied human needs so that tourism destinations are also growing. In addition, tourism actors are also increasingly diverse, including rural communities or better known as community-based tourism. The tourist village is one of the destinations that in recent years has increased demand. Even in Temanggung Regency, tourist villages have become the prima donna of tourism packages. One of these tourist villages is Trah Aji Village in Parakan District. Because of its location in the countryside and the potential it contains needs to be known by prospective travelers, marketing strategy and management are the mainstay of the life and death of this tourist village. This community service activity aims to strengthen marketing management so that the existing potential can be identified and attract tourists, both domestic and foreign, to visit this village. The method used is capacity building through training to tourism village stakeholders on tourism marketing management. The results obtained from this training are increased knowledge of tourism marketing management among stakeholders.